Construction of Scientific Facts – Why is Relativism Essential in Bypassing Incommensurable Gaps in Humanities. Case of Personal Involvement – Biased Scientific Facts - Mulej, Lucija (Qualitative Sociology Review, 2008)
This paper addresses the theory of knowledge in relativistic terms of Paul Feyerabend, stressing the importance of personal involvement in the research and theorizing. Since the topic is a constant and widely accepted premise the author is insisting that it has been actually ignored in the sociology and philosophy of science. It is apparent in discursive form, neglected in actual consequences for science in general. Defending the thesis of relativism had remained unacknowledged by the general scientific community. Biographies of mavericks and their struggle and exclusion from scientific community etc. had been constant in the history of science. Is science nowadays able to accept criticism and implement arguments of knowledge beyond the institutionalized standards? Throughout this article we argue that personal involvement creates biased scientific facts; acknowledging and applying tacit knowledge we move beyond personal involvement and create appropriate interpretations of facts and phenomena under investigation, where we reconsider the construction of facts and personal beliefs, knowing that our fields of expertise are incommensurable.